Study of the Effect of Alkali Metal Ions (Li+, Na+, K+) in Inhibiting the Spontaneous Combustion of Coal - Yunqiu Liu; Hongjie Peng; Ran Peng; Chuanbo Cui (Fuels, 2025)
The essence of coal spontaneous combustion lies in the existence of a large number of chemically active functional groups in the coal molecule, such as aldehyde group (-CHO) and methoxy group (-OCH3) in the side chain structure of coal molecule, which can be easily oxidized, thus triggering the spontaneous combustion process. Retardant is a more widely used technology to prevent the spontaneous combustion of coal, but the research on the microscopic level of the mechanism of coal spontaneous combustion retardation has been weak for many years, so deepening the exploration in this field is crucial for the optimization of the retardation strategy. The inhibition effect of Li+, Na+, and K+ inhibitors was investigated through the programmed warming experiments, and the results showed that the carbon monoxide production and oxygen consumption of coal samples inhibited by Li+, Na+, and K+ inhibitors were reduced to different degrees compared with that of the original coal, which proved that it had an inhibitory effect on the spontaneous combustion of coal. In order to deeply investigate the interaction between the molecular structure properties of coal and alkali metal ions, the complexes formed by three typical alkali metal ions-Li+, Na+, and K+-with specific reactive groups (-CHO and -OCH3) in coal were investigated with the help of the quantum chemical calculation software Gaussian 16W, and the following conclusions were made after analyzing the complexes: on the one hand, the complexes formed by Li+, Na+, and K+ with the reactive groups in coal can occupy the sites where the reactive groups bind with oxygen, reduce the chance of coal oxygen contact and inhibit its oxidation process; on the other hand, the coordinating action of alkali metal ions increases the maximum energy barrier that needs to be overcome for the reaction of the originally active groups, resulting in the coal molecules in the process of oxidation reaction, increasing the difficulty of the reaction, thus effectively curbing the tendency of spontaneous combustion of coal.